Determination of (0,2)-regular sets in graphs and applications - Pacheco, Maria F. (2014)
A (k,τ)-regular set in a graph is a subset of vertices inducing a k-regular subgraph and such that each vertex not in the set has exactly τ neighbours in it. We will present a new algorithm for the determination of (0,2)-regular sets as well as its application to the determination of maximum matchings in arbitrary graphs.